"Apologies" from Pathologists: Why, When, and How to Say "Sorry" After Committing a Medical Error. (May 2014) - Dewar, Rajan; Parkash, Vinita; Forrow, Lachlan; Truog, Robert D.
How pathologists communicate an error is complicated by the absence of a direct physician–patient relationship. Using 2 examples, we elaborate on how other physician colleagues routinely play an intermediary role in our day-to-day transactions and in the communication of a pathologist error to the patient. The concept of a "dual-hybrid" mind-set in the intermediary physician and its role in representing the pathologists' viewpoint adequately is considered. In a dual-hybrid mind-set, the intermediary physician can align with the patients' philosophy and like the patient, consider the smallest deviation from norm to be an error. Alternatively, they might embrace the traditional physician philosophy and communicate only those errors that resulted in a clinically inappropriate outcome. Neither may effectively reflect the pathologists' interests. We propose that pathologists develop strategies to communicate errors that include considerations of meeting with the patients directly. Such interactions promote healing for the patient and are relieving to the well-intentioned pathologist.